A Micrology of Pattern Recognition in Philip K. Dick’s A Scanner Darkly - Berkay Üstün (Litera:dil,edebiyat ve kültür araştırmaları dergisi, 2023)
This article is a conjointly formal and thematic inquiry dedicated to unpacking the internal coherence of Philip K. Dick’s A Scanner Darkly (1976). Organized around the unifying problem of pattern recognition, the article clarifies the deep congruence that exists between the seemingly unrelated imaginary technologies of the novel, used on both sides of the central demarcation that divides the identity of its protagonist: law enforcement and the trade in controlled substances. While it benefits from concepts designed to investigate science fiction as a genre, it also brings in discourses developed to make sense of media technologies in the real world. Guarding against the danger of eclipsing the text under information about the media historical context, this article allies media theory with narrative analysis and relies on “micrology” as a strategy of selective close reading following the logic of detection, recognition, and the failures thereof in the novel. This manner of inquiry allows me to specify the nature of pattern recognition as a lost capacity in the narrative arc, tracking the problems of information theory and the decline of cognitive capacities, as well as demonstrating their immanence to a single complex of ideas. In this sense, what belongs to intellectual history in the following discussion, is subject to the requirement that it makes the technological and psychological aspects of the narrative more intelligible and respond to the unique challenges of its combination of estranging world-building and all too familiar countercultural tropes.